Melancia é fruta? Um estudo sobre encontros e desencontros nas relações médico pacientes em Jaguari - RS - Bolzan, Helen Lúci Taschetto (2011)
The relationship between doctors and patients are represented by two individuals, many times, cultural and socially disconnected. The social actor acts interpreting the world that surrounds him/her according to some values, beliefs and perceptions transmitted by the reality socially constituted. Patients normally understand the illness according their daily activities, point of view and experiences. On the other hand, doctors are basing their ideas in the occidental culture, in the hegemonic biomedical model, build based on Cartesian s ideas, on mind-body dichotomy and on scientific rationality. In this meeting, many social representations are building along a clinical consultation. This research aims to understand patients perceptions about their illness, concerning the reasons why it happened, the cure expectations and their opinion about the consultation. In order to carry out this study, a qualitative methodology was used based on observations in the waiting room and interviews to collect the data. The speech acts revealed in the interviews were analyzed based on Lefrèvre & Lefrèvre ideas about the Collective Subject Discourse. The research revealed that patients obey the doctors because they believe in the moral and technical authority of the professionals. In the majority of the cases, the doctor s orientations are followed, unless they face economic obstacles or problems in the understanding of the orientations. At the same time that patients criticize the doctors attendance, they know how to recognize the legitimate and traditional medical practice. In conclusion, the study revealed that, according to the patients, the best kind of health professional is the one that supports a distant relationship during the consultation, avoid contact with the patient and utilizes a technical language to prescribe the medicine reinforcing his/her role as a social authority to the State and to society.